ILMU BUDAYA DAN METODOLOGINYA Bagaimana Ilmu Budaya Menghadapi Perubahan Episteme? - Haryatmoko Haryatmoko (Sunan Kalijaga State Islamic University Yogyakarta, 2012)
This research focuses on how to comprehend cultural study scientifically. In elaborating cultural studies, the main problem lies on digesting reality, which will not be simple. In addition, a certain construct of cultural studies emerges as well as its models of elaboration. By using Gilles-Gaston Granger framework, on the relationship between the object of the study and human comprehension three models of explanation are explained. Those models are energetics, cybernetics, and semantics. The first two models are closer to natural science. These models also tend to be reductive and deterministic. The last model tends to be closer to cultural studies because it touches the actions of human, which needs to be interpreted.